PROBLEMS OF FORMATION OF ACCOUNTING PROCESSES ON THE BASE OF DIGITAL TECHNOLOGIES (American Journal of Pedagogical and Educational Research, 2024)
The advent of digital technologies has revolutionized the way businesses operate, and the accounting profession is no exception. The formation of accounting processes on the basis of digital technologies has brought about numerous benefits, including increased efficiency, accuracy, and transparency. However, this transformation is not without its challenges. This article will delve into the problems associated with the formation of accounting processes on the basis of digital technologies.